Tecnologias de informação e comunicação e o ambiente meseológico: um estudo do discurso tecnológico dos periódicos - Zagatto, Vanessa Alves [UNESP] (2013)
The Information and Communication Technologies are largely responsible for the dissemination of information,in addition to enabling access, use and retrieval of information in different environments. Thus, maximizing the communication process and the flow of information. In this sense, it is pertinent to develop a study on research published in journalsIS (Information Sciense), with the intention to observe the studies and forms of application of Information and Communication Technologies ( ICT ) in the area . The general objective of this research is to identify the discourse on ICT in journals of information science, the possibilities outlined by the introduction of technologies in environments of museums, and what aspects of the environment in the museum Web identified in the theoretical framework. There was a previous selection of eleven journals,as initial selection criteria to ensure the academic nature of the research, we used the Qualis CAPES, which determines the criteria for evaluating qualitative indices as periodic assessment of the Coordination of Improvement of Higher Education Personnel. The margin index of Qualiswere selected from A1 to B3 to ensure the qualitative study. The Web is a tool that allows the museum to present their services through interactive and visual resources, whether in an institution created in a virtualenvironmentorto documents and information incorporated into the virtual environment.It was be consideredrelevant form of representation of information and services of the institution on the Web, whether a museum exists only in virtual contextor just a way to promote the institution asseen in institutional Websites.